Letter to the Editor: COVID-19: Isolations, Quarantines and Domestic Violence in Rural Areas - Caio Augusto de Lima; Paula Monikee Rezende Alves; Carla Jaciara Baraúna de Oliveira; Thaísa Rodrigues Nascimento de Oliveira; Katricia Beatriz Barbosa; Henrique Cardoso Marcene; Stefan Vilges de Oliveira (Ital Publication, 2020)
It was argued that the coronavirus pandemic is likely to lead to an increase in the occurrence of domestic violence incidents against women, while victims are forced to quarantine at home with potentially abusive family members. In this context, it was found that women living in rural areas are at increased risk. In defining their vulnerability was observed least school years, black race and young age (young women) of raped and abused women. The spouse was also identified as the main aggressor, who practiced physical violence, with recurrence, within the victim's own residence, associated with the abusive use of alcoholic beverages. It has alerted the world to this problem and called attention to the need to promote strategies to protect women. It is known that women and men experience pandemics in different ways and those circumstances, in addition to strengthening situations of women's vulnerability, tend to aggravate family tensions, especially in families with a history of recurrent domestic violence.